Multilocus Sequence-Based Analysis Delineates a Clonal Population of Agrobacterium (Rhizobium) radiobacter (Agrobacterium tumefaciens) of Human Origin - Aujoulat, Fabien (American Society for Microbiology, 2011)

(untitled)
The genus Agrobacterium includes plant-associated bacteria and opportunistic human pathogens. Taxonomy and nomenclature within the genus remain controversial. In particular, isolates of human origin were all affiliated with the species Agrobacterium (Rhizobium) radiobacter, while phytopathogenic strains were designated under the synonym denomination Agrobacterium tumefaciens. In order to study the relative distribution of Agrobacterium strains according to their origins, we performed a multilocus sequence-based analysis (MLSA) on a large collection of 89 clinical and environmental strains from various origins. We proposed an MLSA scheme based on the partial sequence of 7 housekeeping genes (atpD, zwf, trpE, groEL, dnaK, glnA, and rpoB) present on the circular chromosome of A. tumefaciens C58. Multilocus phylogeny revealed that 88% of the clinical strains belong to genovar A7, which formed a homogeneous population with linkage disequilibrium, suggesting a low rate of recombination. Comparison of genomic fingerprints obtained by pulsed-field gel electrophoresis (PFGE) showed that the strains of genovar A7 were epidemiologically unrelated. We present genetic evidence that genovar A7 may constitute a human-associated population distinct from the environmental population. Also, phenotypic characteristics, such as culture at 42°C, agree with this statement. This human-associated population might represent a potential novel species in the genus Agrobacterium.